2020
DOI: 10.3389/fpubh.2020.00442
|View full text |Cite
|
Sign up to set email alerts
|

The Extent to Which Menstruation-Related Issues Are Included in Graduate-Level Public Health Curricula

Abstract: Objectives: Menstruation is increasingly recognized as an issue in domestic and global public health. Public health graduates of U.S. schools of public health must have adequate competencies to address menstruation and its implications for health and well-being in their future endeavors in research, practice and policy. This study sought to understand the extent to which U.S. schools currently integrate menstruation-related content (menstrual health, menstrual hygiene, etc.) and related competencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…The medicalization of women has already been discussed in the literature [ 24 , 25 , 38 , 63 , 64 ]. Unsurprisingly, menstruation has for a long time been constructed as a “health issue” in need of medicalization [ 64 ] and has been critically under-addressed in public health [ 23 ]. This points to the importance of reframing menstruation as a vital sign of health [ 1 ], which does not seem implemented in clinical practice based on our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The medicalization of women has already been discussed in the literature [ 24 , 25 , 38 , 63 , 64 ]. Unsurprisingly, menstruation has for a long time been constructed as a “health issue” in need of medicalization [ 64 ] and has been critically under-addressed in public health [ 23 ]. This points to the importance of reframing menstruation as a vital sign of health [ 1 ], which does not seem implemented in clinical practice based on our results.…”
Section: Discussionmentioning
confidence: 99%
“…Even if community-based education should be promoted, the population should have better access to accurate menstruation-related information and knowledge. University curricula on healthcare, public health and education professions should also incorporate MH and MI as public health issues [ 18 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 2020 study conducted by the Columbia Mailman School's Gender, Adolescent Transitions, and Environment (GATE) Program identified a significant gap in the education of future graduate level public health professionals (Sommer et al, 2020b).…”
Section: Professional Educationmentioning
confidence: 99%
“…Their review of top US schools' public health curricula showed notable gaps around menstrual health (Sommer et al, 2020b). In response to their study, researchers at the GATE Program launched a freely accessible and comprehensive online course covering a wide variety of topics related to menstruation across the globe (Columbia Mailman School of Public Health, 2021).…”
Section: Professional Educationmentioning
confidence: 99%
See 1 more Smart Citation